The Influence of Affective Feedback Adaptive Learning System on Learning Engagement and Self-Directed Learning - Liu, Hsin-Lan; Wang, Tao-Hua; Lin, Hao-Chiang Koong; Lai, Chin-Feng; Huang, Yueh-Min (Frontiers in Psychology, 2022)
The outbreak of the two-year corona virus has made a great difference on existing methods of learning and instruction. Online education has become a crucial role to maintain non-stop learning after the post-epidemic period. The advanced technologies and growing popularity of network equipment have made it easy to deploy remote connections. However, teachers still face challenges when they actually implement distance courses. Classroom interaction plays an impetus role to affect learning while active learning is key to engage students in the process of learning and increase academic success. Therefore, the current study established a learning system that aimed to understand learners’ emotional signals during learning by applying the adaptive-feedback emotional computing technology. The purpose of the system was to allow learners to 1) self-examine their learning condition, 2) enhance their self-directed learning, 3) help learners who are in negative learning emotions or settings to lower anxieties and 4) promote their learning attitudes and engagement. Result showed that the system with the adaptive-feedback emotional computing technology has significantly improved the learning effectiveness, lowered learning anxieties and increased students’ self-directed learning.